Carbonylative Suzuki Coupling Reaction Catalyzed by a Hydrospirophosphorane Palladium Complex. Issue 23 (15th November 2017) - Wójcik, Przemysław; Sygellou, Labrini; Gniewek, Andrzej; Skarżyńska, Anna; Trzeciak, Anna
Abstract: A Pd complex with the H‐spirophosphorane ligand, PdCl2 {P(OCMe2 CMe2 O)OC6 H4 NH2 } (Cat. 1), was used as the catalyst in the carbonylative Suzuki coupling of substituted iodobenzenes with arylboronic acids and with sodium tetraphenylborate. Substituted diarylketones were obtained in good to excellent yields and a selectivity over 95 % under 1 atm of CO with 1.5 mol % of the catalyst. The promoting role of the H‐spirophosphorane ligand in the catalytic process was evidenced. We used X‐ray photoelectron spectroscopy, TEM, and 31 P NMR spectroscopy to reveal that during the reaction Cat. 1 undergoes transformation into Pd complexes that bear the spirophosphorane ligand or other P ligands formed by its dealkylation and to Pd nanoparticles. All these Pd species contribute to the high productivity of the system. Abstract : Cocktail hour : The "cocktail‐type" catalytic system that contains Pd complexes and Pd nanoparticles with the H‐spirophosphorane ligand is highly efficient in carbonylative Suzuki coupling under mild conditions.